A novel class of oral, non-immunosuppressive, beta cell-targeting, TXNIP-inhibiting T1D drugs is emerging - Jing, Gu; Jo, SeongHo; Shalev, Anath (Frontiers in Endocrinology, 2024)
Diabetes treatment options have improved dramatically over the last 100 years, however, close to 2 million individuals in the U.S. alone live with type 1 diabetes (T1D) and are still dependent on multiple daily insulin injections and/or continuous insulin infusion with a pump to stay alive and no oral medications are available. After decades of focusing on immunosuppressive/ immunomodulatory approaches for T1D, it has now become apparent that at least after disease onset, this by itself may not be sufficient, and in order to be effective, therapies need to also address beta cell health. This Perspective article discusses the emergence of such a beta cell-targeting, novel class of oral T1D drugs targeting thioredoxin-interacting protein (TXNIP) and some very recent advances in this field that start to address this unmet medical need. It thereby focuses on repurposing of the antihypertensive drug, verapamil found to non-specifically inhibit TXNIP and on TIX100, a new chemical entity specifically developed as an oral anti-diabetic drug to inhibit TXNIP. Both have shown striking anti-diabetic effects in preclinical studies. Verapamil has also proven to be beneficial in adults and children with recent onset T1D, while TIX100 has just been cleared by the U.S. Food and Drug Administration (FDA) to proceed to clinical trials. Taken together, we propose that such non-immunosuppressive, adjunctive therapies to insulin, alone or in combination with immune modulatory approaches, are critical in order to achieve effective and durable disease-modifying treatments for T1D.